(untitled) (Journal of Fiber Bioengineering and Informatics, 2024)
This paper thoroughly reviews the current state of digital simulation technology and its strategic implementation across applications, primarily focusing on advanced compression garments. Despite the significant impact of three-dimensional digital garment simulators (3DGS) on the apparel and textile industry, their usage has largely been confined to visual prototyping, visual quality check, or marketing tools. Notably, these simulators’ physical or mechanical representation has been understated in the context of advanced functional manufacturing. This review delves into the potential strategic integration of virtual physical properties to augment garment functionalities, particularly within wearables and medical-grade compression fields. The initial phase of this study provides a comprehensive overview of the status of 3D garment simulation tools and their digitisation capabilities. Subsequently, a gap analysis focuses on minimising disparities between simulated and actual physical property assessments. Despite the absence of reliability and standardised testing within a virtual environment, this paper focuses on the relevant literature to gain crucial insights for apparel and textile engineers, providing a nuanced understanding of the capabilities and limitations of 3DGS mechanical representation in enhancing advanced functionalities, specifically customised for diverse end-users.